1992
DOI: 10.1088/0022-3727/25/2/027
|View full text |Cite
|
Sign up to set email alerts
|

Triboemission of charged particles and photons from solid surfaces during frictional damage

Abstract: Triboemission is defined as the emission of electrons, ions, photons and neutral particles during tribological surface damage. Triboemission of negatively and positively charged particles and photons by the wearing of solid surfaces of metals, ceramics, glass, anodic aluminium oxide films (Al2O3), polymers and mica were studied using a special triboemission measuring apparatus which permits the simultaneous measurement of negatively and positively charged particles, photons and friction coefficients in a vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 4 publications
6
45
0
Order By: Relevance
“…20 Triboemitted charge carriers of both polarities have been detected in experiments for different insulating materials, and the quantity of emitted charge carriers has been found to increase for higher loads (∼1 N) and surface damage. 110,111 The triboemitted electrons rapidly react with the rubbing materials to form free radicals and negative ions, rendering the rubbed surface highly reactive and thereby inducing tribochemical reactions. 20 The quantity of ion and radical formation by cutting or grinding of polymers has been determined by electron spin resonance measurements (see Table II).…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…20 Triboemitted charge carriers of both polarities have been detected in experiments for different insulating materials, and the quantity of emitted charge carriers has been found to increase for higher loads (∼1 N) and surface damage. 110,111 The triboemitted electrons rapidly react with the rubbing materials to form free radicals and negative ions, rendering the rubbed surface highly reactive and thereby inducing tribochemical reactions. 20 The quantity of ion and radical formation by cutting or grinding of polymers has been determined by electron spin resonance measurements (see Table II).…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…Here, an almost constant low emission level is seen, onto which several high bursts of emission are superimposed. As observed by Nakayama et al [12] and Molina et al [16] for alumina specimens, electrons are emitted in bursts, shortly after scratching starts. The coefficient of friction throughout this test was measured at 0.1.…”
Section: Averaged Measurementsmentioning
confidence: 58%
“…In most triboemission studies found in the literature, emission ceases as soon as the scratching stops [12]. For instance, Molina et al observed this for semi-conductors, though they mentioned that significant post-contact emission occurred for insulators [23].…”
Section: Spatially Resolved Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…radio waves; IR, visible, UV light; and X-rays [34]. Significant research in the field of triboemission was carried out by Nakayama et al [35]. Kim et al [36] investigated electron and photon evolvement (phE) from magnesia (MgO) under friction with diamond; they found that during indentation, prior to any fracture of MgO, only phE was observed.…”
Section: Triboemissionmentioning
confidence: 99%